APAKAH LEAN MANUFACTURING MEMEDIASI HUBUNGAN ANTARA CORPORATE GOVERNANCE DAN NILAI PERUSAHAAN? DOES LEAN MANUFACTURING MEDIATE THE RELATIONSHIP BETWEEN CORPORATE GOVERNANCE AND FIRM VALUE? - Jelita, Fernanda Putri; Haryati, Tantina (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2025)
This research explores whether Lean Manufacturing serves as a connecting mechanism between corporate governance practices and firm value. The study adopts a quantitative design and utilizes secondary data obtained from food and beverage sector firms listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. A purposive sampling approach was employed, resulting in 11 companies that met the defined criteria, leading to 55 firm-year observations. Data were analyzed using path analysis through SPSS.The empirical results indicate that the components of corporate governance, namely the proportion of independent commissioners and the presence of an audit committee, do not significantly influence firm value. Likewise, Lean Manufacturing demonstrates no meaningful impact on firm value. Among the governance variables, only independent commissioners have a significant yet negative effect on Lean Manufacturing practices. The mediating role of Lean Manufacturing in the relationship between corporate governance and firm value is not statistically supported, although an indirect path is structurally present. In summary, Lean Manufacturing does not act as an effective intermediary in linking governance mechanisms to firm performance within the examined firms and period